2017
DOI: 10.1111/cea.12920
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic regulatory effects of human umbilical cord blood‐derived mesenchymal stem cells in a murine ovalbumin asthma model

Abstract: Our results suggest that huMSC treatment reduces OVA-induced allergic inflammation, which could be mediated by regulatory T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
2
18
0
1
Order By: Relevance
“…IL-4 can lead to changes in functions of allergic asthma including eosinophil infiltration, airway hyperresponsiveness and mucus overproduction. 42,43 Our results showed that expression of IL-4 decreased following Del-1 administration (Figure 4). It has been recognized that CCL11(eotaxin), a small cytokine belonging to the CC chemokine family, selectively recruits eosinophils by inducing their chemotaxis in allergic asthma.…”
Section: Discussionmentioning
confidence: 74%
“…IL-4 can lead to changes in functions of allergic asthma including eosinophil infiltration, airway hyperresponsiveness and mucus overproduction. 42,43 Our results showed that expression of IL-4 decreased following Del-1 administration (Figure 4). It has been recognized that CCL11(eotaxin), a small cytokine belonging to the CC chemokine family, selectively recruits eosinophils by inducing their chemotaxis in allergic asthma.…”
Section: Discussionmentioning
confidence: 74%
“…The hUC-MSCs can reduce ovalbumin (OVA)-induced allergic inflammation. This effect might be mediated by regulatory T (Treg) cells ( Kang et al, 2017 ). Human mesenchymal stem cells (HUMSCs) can reduce neutrophil airway inflammation by downregulating neutrophil chemokine production and by modulating T-cell responses ( Hong et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…UCB-MSC has a multidirectional immunomodulatory effect on both innate and adaptive immune cells: T lymphocytes and B lymphocytes, dendritic cells and natural killer cells. UCB-MSC exhibit immunosuppressive activity on lymphocyte proliferation and inhibit the pro-inflammatory effect of cytokines [6]. Hu et al (2013) in the results of their research indicate the clinical safety of using Wharton's jelly-derived mesenchymal stem cells from the umbilical cord of patients, as well as the restoration of pancreatic B-cell function in newly diagnosed type I diabetes [7].…”
Section: Treating Type I Diabetesmentioning
confidence: 99%